Economic evaluation of sintilimab plus chemotherapy vs. pembrolizumab plus chemotherapy for the treatment of first-line advanced or metastatic squamous NSCLC - Pingyu Chen; Pingyu Chen; Xintian Wang; Shengwen Zhu; Hongchao Li; Hongchao Li; Mingjun Rui; Yingcheng Wang; Haikui Sun; Aixia Ma; Aixia Ma (Frontiers Media S.A., 2022)
Background and objectiveSintilimab has superior efficacy and safety in patients with advanced or metastatic squamous non-small cell lung cancer (NSCLC), but its cost-effectiveness in China is unclear. This study is to evaluate the cost-effectiveness of sintilimab plus chemotherapy vs. pembrolizumab plus chemotherapy for locally advanced or metastatic squamous NSCLC in China.MethodsFrom the perspective of the Chinese health system, the partitioned survival model with three health states was established in a 3-week cycle and a lifetime time horizon. The two-stage method was used to estimate the overall survival hazard ratios to avoid the bias by crossover design in ORIENT-12 and KEYNOTE-407 studies. The anchored matching adjusted indirect comparison method (MAIC) was used for indirect comparison based on the individual patient data from ORIENT-12 and the publicly published KEYNOTE-407 study due to the lack of head-to-head clinical trials. Only direct medical costs were included, and utilities were derived from the published literature in the base case analysis. Sensitivity analysis was also performed to verify the robustness of the model results. In addition, the scenario analysis where the utilities were derived from the Quality of Life Questionnaire-Core 30 (QLQ-C30) scale in the ORIENT-12 by mapping to the EuroQol-5-dimension 5-level (EQ-5D-5L) was carried out to explore the uncertainty of the results.ResultsCompared with pembrolizumab + chemotherapy, sintilimab + chemotherapy incurred a lower lifetime cost ($12,321 vs. 36,371) and yielded fewer quality-adjusted life-years (QALYs) (0.9902 vs. 1.0085), which resulted in an incremental cost-effectiveness ratio (ICER) of $1,314,208/QALY. A sintilimab strategy is a cost-effectiveness option under the WTP of 1-3 times the GDP per capita in China ($11,250/QALY~$33,749/QALY). The utility value of the post-progression, the unit cost of albumin paclitaxel, and the utility value of the progression-free state were the main drivers in the deterministic sensitivity analysis (DSA). According to the probabilistic sensitivity analysis (PSA), sintilimab + chemotherapy was 100% cost-effective when the WTP was 1-3 times China's per capita GDP. The results of the scenario analysis showed that sintilimab + chemotherapy obtained more QALYs (1.2319 vs. 1.1815) and lower costs ($12,321 vs. 36,371), which implied that sintilimab + chemotherapy may dominate the pembrolizumab + chemotherapy.ConclusionCompared with pembrolizumab + chemotherapy, sintilimab + chemotherapy is more cost-effective for first-line treatment in Chinese patients with locally advanced or metastatic squamous NSCLC.